Increasing the Frequency of Predator Sightings Is the Key to Increasing Rice Production in an Environmentally Friendly Manner - Irpan Sudirman; Rahmat Gunawan; Holidah Fauziah; Wachdijono (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2025)
IncrEasing rice production is essential in Indonesia because most of the population's staple food is rice. However, the chemical efforts made so far are considered not environmentally friendly, so other efforts that are considered more supportive of environmental sustainability, namely biologically by bringing in predators, are needed. This study aims to explore the influence of predators on increasing rice production. The research location is in Maleber Village, Maleber District, Kuningan Regency, West Java Province, Indonesia. The research was conducted during July-December 2024 using a quantitative research design and survey methods. The sample was 120 rice farmers, and the sampling technique was simple random sampling. Data analysis uses the Structural Equation Model (SEM) with the help of the Analysis Model Structural (AMOS) application. The results showed that the presence of predators had a significant effect on increasing rice production (0.96). The most dominant indicator in the variable of predator presence was the frequency of predator sightings (0.87). Therefore, it is recommended that environmentally friendly rice production be increased by increasing the frequency of predator sightings through refugia planting, diversification, and the creation of natural habitats.